Evaluation of white matter hyperintensities and retinal fiber layer, ganglion cell layer, inner-plexiform layer, and choroidal layer in migraine patients - Tak, Ali Zeynel Abidin; Sengul, YILDIZHAN; ŞENGÜL, YILDIZHAN; Bilak, Semsettin (My University, 2018)
The aim of our study is to assess retinal nerve fiber layer (RNFL), the ganglion cell layer (GCL), inner-plexiform layer (IPL), and choroidal layer in migraine patients with white matter lesion (WML) or without WML, using spectral domain optical coherence tomography (OCT). To our study, 77 migraine patients who are diagnosed with migraine in accordance to the International Classification of Headache Disorders (ICHD)-3 beta and 43 healthy control are included. In accordance to cranial MRI, migraine patients are divided into two groups as those who have white matter lesions (39 patients), and those who do not have a lesion (38 patients). OCT was performed for participants. The average age of participants was comparable. The RNFL average thickness parameter in the migraine group was significantly lower than in the control group (p < 0.01). However, no significant difference was detected among those migraine patients who have WML, and those who do not have. No significant difference is detected among all groups in terms of IPL, GCL, and choroidal layer measuring scales. The proofs showing that affected retinal nerve fiber layer are increased in migraine patients. However, it is not known whether this may affect other layers of retina, or whether there is a correlation between affected retinal structures and white matter lesions. In our study, we found thinner RNFL in migraine patients when we compared with controls but IPL, GCL, and choroid layer values were similar between each patient groups and controls. Also, all parameters were similar between patients with WML and without WML. Studies in this regard are required.